Analisis Hasil Sasaran Kinerja Pegawai pada BPSIP Banten - Nepi Andriani; Ananda Nur Amalia; Syamsul Hidayat (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
This research aims to analyze the results of employee performance targets at the Banten Government Human Resources Development Center (BPSIP), as well as the factors that influence the achievement of this performance. This research uses a qualitative approach with a case study at BPSIP Banten, which collects data through in-depth interviews, observations and document analysis related to employee performance results. The research results show that although the majority of employees have succeeded in meeting the performance targets set, there are still several obstacles that affect achievement, such as lack of coordination between work units, limited facilities and resources, and low motivation for some employees. Based on these findings, this research provides recommendations for improving the effectiveness of the performance management system at BPSIP Banten, including increasing coordination between work units, employee motivation, and providing more adequate resources.